Successful Aging as the Intersection of Individual Resources, Age, Environment, and Experiences of Well-being in Daily Activities. (1st March 2017) - Mejía, Shannon T.; Ryan, Lindsay H.; Gonzalez, Richard; Smith, Jacqui
Abstract: Objective: We conceptualize successful aging as a cumulative index of individual resources (the absence of disease and disability, high cognitive and physical functioning, social embeddedness) in the service of successful aging outcomes (global well-being, experienced well-being, and vital status), and conditioned by age, social structure, and environment. Method: The study used baseline and follow-up data from the 2008–2014 waves of the Health and Retirement Study ( N = 17, 230; age = 51–101). Linear, multilevel, and logistic models compared individual resources at baseline as independent, cumulative, and binary predictors of outcomes 4 years later. Results: Individual resources were unequally distributed across age group and social structures (education, wealth, race, gender) and had a cumulative effect on all successful aging outcomes. For experienced well-being, individual resources were most important at midlife and for groups with lower education. Person–environment congruence (social cohesion, city satisfaction) was associated with all successful aging outcomes and conditioned the effect of individual resources on experienced well-being. Discussion: A cumulative index allows for gradations in resources that can be compensated for by external factors such as person–environment congruence. This index could guide policy and interventions to enhance resources in vulnerable subgroups and diminish inequalities in successful aging outcomes.